Importancia del manejo integrado de Demotispa neivai bondar en el cultivo de palma aceitera (Elaeis guineensis, Jacq.) en Ecuador - Rojas Mantilla, Norma (2022)
This document refers to the importance of integrated management of Demotispa neivai in oil palm cultivation in Ecuador. The conclusions determine that the cultivation of oil palm constitutes one of the main agro-industrial items, showing, due to its high demand in the market for products and by-products derived from it; the larvae live between the fruits of the green clusters and the base of the arrows; during the day the larvae remain between the spikes of the bunch, feeding on the fleshy part of the spathe, in the area surrounding the bunch peduncle and also scraping the bracts. Integrated management of D. neivai includes different agricultural practices, in addition chemical insecticides can be applied by root route or as stem injection, but these cause environmental damage and in turn eliminate beneficial organisms and currently botanical insecticides are being used to based on citrus extract or biological controls based on bacteria such as Baeuveria sp. and D. neivai is a pest that directly affects production, the adult can consume 1.5 cm2 of the epicarp of the fruit each day. The scraping that it does on the fruits causes losses due to the confusion that it causes producers to recognize the degree of maturity of the bunches at the time of harvest and as a consequence the decrease in oil extraction, its potential can reach up to 24 %, but when the cluster shows 50% damage caused by the insect, this potential can be reduced by 1.04%.